PENGEMBANGAN POTENSI PESERTA DIDIK: PERSPEKTIF DOMAIN PENDIDIKAN BENJAMIN S. BLOOM - Jannah, Sitti Riadil (Universitas Islam Negeri Alauddin Makassar, 2022)
The figure of Benjamin S. Bloom is an educational psychologist who has inspired a lot of education with a set of axiomatic frameworks that underlie it. The educational domain which is built on the cognitive, psychomotor, and affective domains has become a major contribution in developing the potential of students. These three domains must be applied in the educational process as an inseparable unit. In this process, educators as educators must be able to understand how the potential for immanent nature in the process of student growth and development continues to develop dynamically. As a leading agent in the transformation of educational values ​​to students in classrooms, the implications of the position of educators as educators in fostering students are very large and the impact can be felt immediately for students.